2020
DOI: 10.3390/horticulturae6040060
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Bioactive Characterisation of Edible and Waste Parts of “Piel de Sapo” Melon

Abstract: Several scientific studies point fruits as rich sources of antioxidants but mainly focus on their edible part. However, fruits wastes are abundant sources of bioactive compounds and nutrients, which are considered to be health beneficial. The main purpose was to characterise juice, pulp, peel and seeds of Piel de Sapo melon, in terms of several physicochemical characteristics (soluble solids content, titratable acidity, pH, potassium, colour and water activity), some bioactive compounds (total phenolics, vitam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
(50 reference statements)
2
12
1
Order By: Relevance
“…The flour presented a much higher amount (377.36 mg/100 g) than that found in fresh albedo (94.34 mg/100 g). These results were higher compared to the research by Miller et al (2020) with melon rinds that obtained in the flour (29.3 mg/100 g) content four times higher than that found in the flavedo/albedo (18 mg/100 g). Therefore, the flour had a significant content of vitamin C, and when considering its importance as an essential nutrient for human health, it can be used as an indicator of food quality, with its antioxidant properties and protection of the organism from oxidative stress.…”
Section: Concentration Of Bioactive Compoundscontrasting
confidence: 71%
See 3 more Smart Citations
“…The flour presented a much higher amount (377.36 mg/100 g) than that found in fresh albedo (94.34 mg/100 g). These results were higher compared to the research by Miller et al (2020) with melon rinds that obtained in the flour (29.3 mg/100 g) content four times higher than that found in the flavedo/albedo (18 mg/100 g). Therefore, the flour had a significant content of vitamin C, and when considering its importance as an essential nutrient for human health, it can be used as an indicator of food quality, with its antioxidant properties and protection of the organism from oxidative stress.…”
Section: Concentration Of Bioactive Compoundscontrasting
confidence: 71%
“…This behaviour in the flour may be associated with the temperature to which this product was subjected to dehydration, since chlorophyll a is thermally more unstable than chlorophyll b (Pareek et al, 2017). In the study by Miller et al (2020), the melon rind showed higher values than this research. The content of chlorophyll a (57.50 ± 6.27 µg/g) was almost twice as high as that of chlorophyll b (30.36 ± 4.32 µg/g).…”
Section: Concentration Of Bioactive Compoundsmentioning
confidence: 48%
See 2 more Smart Citations
“…Several studies focused on the recovery of the phenolic fraction by conventional alcoholic extraction [ 8 , 14 , 40 ], aqueous wet grinding [ 41 ] or ultrasound assisted extraction [ 42 ] have also been reported. More recent studies [ 11 , 43 ] evaluated the extraction of bioactive compounds (total phenolics, chlorophylls, total carotenoids and vitamin C) from several melon parts by ultra-turrax homogenization in alcoholic media.…”
Section: Introductionmentioning
confidence: 99%